Model Analysis of Heat Transfer by Hammerstein systems and optical instrumentation. Issue 1 (2019) - Garcés, Hugo O.; Palma, Jonathan M.; Rojas, Alejandro J.; Valdebenito, Victor
Abstract: Heat transfer is the core of a combustion process. In the present work, motivated by the recent inclusion of optical instrumentation to perform in situ analysis or combustion diagnostics, we consider the modeling and control of heat transfer by total radiation Radt, by taking information from Hammerstein and LTI modeling. We analyze the overall H∞ -norm performance in open-loop and closed-loop, calculated around specific operational conditions for Hammerstein nominal model. From the results, we verify a significant uncertainty, and simultaneously we propose a robust closed-loop control of the Hammerstein nominal model able to handle the uncertainty in the models.